What do Cochrane systematic reviews say about probiotics as preventive interventions? - Vinícius Lopes Braga; Luana Pompeu dos Santos Rocha; Daniel Damasceno Bernardo; Carolina de Oliveira Cruz; Rachel Riera (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Probiotics have been used for a range of clinical situations and their use is strongly encouraged by the media worldwide. This study identified and summarized all Cochrane systematic reviews about the preventive effects of probiotics in clinical practice. DESIGN AND SETTING: Review of systematic reviews, conducted in the Discipline of Evidence-Based Medicine, Escola Paulista de Medicina (EPM), Universidade Federal de São Paulo (Unifesp). METHODS: We included all Cochrane reviews on any probiotics when they were used as preventive interventions and compared with no intervention, placebo or any other pharmacological or non-pharmacological intervention. RESULTS: 17 Cochrane systematic reviews fulfilled our inclusion criteria and were summarized in this report. None of the reviews included in the present study provided high-quality evidence for any outcome. The benefits from use of probiotics included decreased incidence of antibiotic-associated diarrhea and Clostridium difficile-associated diarrhea; decreased incidence of upper respiratory tract infections and duration of episodes; decreased need for antibiotics and absences from school due to colds; and decreased incidence of ventilator-associated pneumonia. Probiotics seem to decrease the incidence of gestational diabetes mellitus, birthweight, risk of vaginal infection and incidence of eczema. CONCLUSION: Despite the marketing and the benefits associated with probiotics, there is little scientific evidence supporting the use of probiotics. None of the reviews provided any high-quality evidence for prevention of illnesses through use of probiotics. More trials are needed to gain better knowledge of probiotics and to confirm when their use is beneficial and cost-effective.